A Regulatory Delegation Compliance Model for Law Number 1 of 2009 on Aviation: Optimising the Formation of Just and Legally Certain Implementing Regulations - Daniel Dewantoro Rumani; Ahmad Ahmad; Upik Mutiara (SKYHAWK : Jurnal Aviasi Indonesia, 2026)
Law Number 1 of 2009 on Aviation functions as an umbrella statute that delegates extensive technical matters to implementing regulations. This article examines the delegation of rule-making authority under the Law and proposes a Regulatory Delegation Compliance Model (RDCM) to improve the formulation and implementation of subordinate legislation. Using normative legal research with statutory, conceptual, historical, and comparative approaches, the study analyses the construction of delegated authority, the implementation of delegation mandates, and their implications for Indonesia’s aviation legal system. The findings reveal that, although the delegation framework is comprehensive, it lacks clarity regarding the division of authority between Government Regulations and Ministerial Regulations, while sub-delegation often occurs without an explicit statutory basis, creating tension with the principle delegatus non potest delegare. The study also identifies substantial non-compliance with Article 466, as many implementing regulations were issued beyond the statutory deadline or remain absent, creating legal uncertainty and regulatory gaps. To address these issues, the proposed RDCM integrates five sequential functions—formulate, plan, assess, enact, and monitor—grounded in legal certainty, regulatory hierarchy, and the rechtsstaat.